2017
DOI: 10.1039/c7ob02300f
|View full text |Cite
|
Sign up to set email alerts
|

Selective C–H bond electro-oxidation of benzylic acetates and alcohols to benzaldehydes

Abstract: A chemical oxidant-free and mediator-free, direct electro-oxidation of both benzylic alcohols and benzylic esters are reported. The scope of the reaction is explored as a function of both steric and electronic effects. Expansion of the scope to non-benzylic and heteroaryl substrates is investigated. Functionalisation of esters and alcohols selectively to the aldehyde oxidation level using a traceless electron approach is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(10 reference statements)
1
17
0
Order By: Relevance
“…Placement of a strong electron donating group in the ortho , meta or para positions (entry 8), led to the recovery of starting material in all cases. A reason for this may be due to the formation of a methoxy radical (in preference to tertiary amide oxidation) which may redox shuttle unproductively at the working and counter electrodes . To test this hypothesis, 1 i ( m ‐OMe) was subjected to analogous reaction conditions in a sintered glass frit divided H‐cell…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Placement of a strong electron donating group in the ortho , meta or para positions (entry 8), led to the recovery of starting material in all cases. A reason for this may be due to the formation of a methoxy radical (in preference to tertiary amide oxidation) which may redox shuttle unproductively at the working and counter electrodes . To test this hypothesis, 1 i ( m ‐OMe) was subjected to analogous reaction conditions in a sintered glass frit divided H‐cell…”
Section: Resultsmentioning
confidence: 99%
“…The ubiquitous nature of the amide bond found both in nature; agrochemicals and drug molecules (Figure ) necessitated the development of a late‐stage electrosynthetic N ‐dealkylation method described herein. The Shono‐type oxidation manifold of amides coupled with the reported in situ collapse of ɑ‐oxidised intermediaries in the oxa‐Shono reaction prompted us to consider the generality of this reaction manifold for tertiary amide N ‐dealkylation.…”
Section: Introductionmentioning
confidence: 99%
“…The deuterated solvents used for NMR analysis were: chloroform (CDCl 3 : δH 7.26, δC 77.2), dimethyl sulfoxide (d 6 -DMSO: δH 2.50, δC 39.5), and deuterium oxide (D2O: δH 4.79). Coupling constants are given in Hertz (Hz) 27 . All individual signals were assigned using 2D NMR spectroscopy ( 1 H-1 H-COSY, 1 H-13 C-HSQC, and 1 H-13 C-HMBC).…”
Section: Methodsmentioning
confidence: 99%
“…1 H and 13 C-NMR spectra were recorded on a JEOL ECS 400 MHz NMR spectrometer. 1 H and 13 C NMR chemical shifts (δ) are reported in parts per million relative to tetramethylsilane (TMS), with the solvent resonance employed as the internal standard (CDCl 3 at 7.26 ppm, CDCl 3 at 77.2 ppm).…”
Section: General Pointsmentioning
confidence: 99%
“…Our interest in connecting the voltammetric behaviour of drug molecules to their biological properties is derived from our research into the electrochemistry of small molecules [12][13][14] and adverse drug reactions [15,16]. Recent disparate research has found connections between the redox behaviour of a drug and its biological potency [17][18][19] and the oxidation potential and toxicity of MDMA (Ecstasy) derivatives [20,21] and thiobenzamides [22], and voltammetric studies for assessing electrogenerated drug metabolisms [23] as well as a study of xeniobiotics in the environment [24].…”
Section: Introductionmentioning
confidence: 99%